1991
DOI: 10.1007/bf02011037
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal ultrasonography in infants and children: Pathological findings

Abstract: In a previous paper, the normal sonographic anatomy of the larynx has been described. The pathological findings of this method, its advantages and its drawbacks are now discussed and compared to endoscopy and plain films. It appears to be a very interesting method for functional disorders and space-occupying lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Many studies have noted the fact that despite the desire for support, few women actively seek support themselves. Few seek support groups (Tunaley, Slade & Duncan, 1993) or associations (Nikcevic et al, 1998) and consulting psychological professionals is rare (Garel & Legrand, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have noted the fact that despite the desire for support, few women actively seek support themselves. Few seek support groups (Tunaley, Slade & Duncan, 1993) or associations (Nikcevic et al, 1998) and consulting psychological professionals is rare (Garel & Legrand, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Unsedated endoscopic procedures can permit short structural evaluations and are dependent on greater subject cooperation which is likely in adults [4,7] but not likely in infants or children [11][12][13]. Though sedation and anesthesia make the procedures more tolerable, their use may compromise the functional evaluation of the upper airway, particularly the laryngeal adduction or abduction during swallowing or phonation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Friedman et al [11] established the role of laryngeal ultrasound in delineating the vocal fold movement in a lamb model as well as in infants and children with vocal cord palsy. Garel et al [12] evaluated the glottis using USG, with prior knowledge of endoscopic findings in a nonblinded manner, and found USG to be useful in the evaluation of the inner structures of the larynx and its dynamic function. Vats et al [13] showed good correlation by observers blinded to one of the modalities with ultrasound and direct laryngeal examination in children investigated for vocal cord palsy under anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this approach has also been used to investigate both laryngeal elevation during swallowing in adults [44] and laryngeal pathology in both infants and children [45]. Unfortunately, these ultrasound techniques require both a linear array transducer and an anterior approach to the neck and thus are not feasible for the young breast-feeding infant due to the necessity of close contact of the ventral surface of the infant with the mother to achieve effective breast-feeding [33].…”
Section: Discussionmentioning
confidence: 99%